Memory And Back Identity In The Michael Ondaatje’s War Light - M, Kavitha.; Veerappa. K, Brinda (International Journal of Psychosocial Rehabilitation, 2020)
Memory schemata are a concrete operation in identity formation. Memory activity is based on the basic contrast between the past and the present. Sense of nostalgia, displacement, loss of identity, dilemma, connecting roots of the identity formation. Connected with roots overpour the burden of individual identity. Everybody carries the scars, injustices, and wounds of the past with them as they remain in their memories and the places they formerly owned. Michael Ondaatje’s War Light (2018) offers to understand how characters and their identities are created with the aid of memory. The object of this paper is how memory, i.e., back identity, plays a remarkable role in shaping identity. The approach will use postcolonial ideas to analyze the works of my author.